Role of Transvaginal Ultrasonography in the evaluation of Uterine Fibroids: a regional observation in Bangladesh - Mukthadira, -; Hira, MutaTah; Kumer Sharma, Netay; Rahman, ASM Mahbubur; Razzaque, MA; Hossain, Md Zakir; Farzana, MN; Naznin, Rubiat; Hossain, Maria (Community Based Medical Journal, 2018)
Uterine fibroids, also known as leiomyomas, are the most common uterine neoplasms. Although benig, they can be associated with a significant number of morbidity and are the most common indication for hysterectomy. Transvaginal ultrasonography (TVS) has become essential in the diagnosis and management of the uterine fibroids. TVS provides a detailed examination of uterus and ovaries. However, there is no nation-wide and regional clinical study on the use of TVS for the evaluation of uterine fibroids in Bangladesh. In this work, a cross-sectional study toob serve the role of TVS in the evaluation of uterine fibroids in a region of Bangladesh (Greater Mymensingh). In the diagnosis of uterine fibroids by TVS, we observed that 35(81.4%) cases (out of 43) are fibroids and 8 (18.6%) cases are non-fibroids. In histopathological diagnosis, we found 36 (83.7%) cases are uterine fibroids, and 7 (16.3%) cases are without fibroids. In this study, TVS diagnosed uterine fibroids with a sensitivity of 94.4%, the specificity of 85.71%, the accuracy of 97.6%, the positive predictive value of 97.1% and negative predictive value of 75%. The results demonstrate that TVS has the potential to become a useful imaging tool for the evaluation of uterine fibroids. CBMJ 2018 July: Vol. 07 No. 02 P: 17-23